Distributed data-centric maintenance and management layer for WSN = Rozproszona, zorientowana na dane warstwa konserwacji i zarządzania WSN - Zielony, Przemysław; Piotrowski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
Managing wireless sensor networks (WSNs) requires effective node monitoring. This work discusses an approach based on the modular middleware tinyDSM. Through services and adapters, tinyDSM allows to adapt to various needs and control operations on nodes and in the network. By using and monitoring state machines at every level of the software architecture enables node monitoring, increasing system reliability and fault tolerance. This also contributes to scalability and adaptability to different environmental conditions, ensuring optimal resource utilization in various applications. Additionally, the ability to notify users and share data facilitates communication and troubleshooting, enables quick resolve to network errors.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne